2022
DOI: 10.11613/bm.2022.030801
|View full text |Cite
|
Sign up to set email alerts
|

Acquired hemophilia A secondary to SARS-CoV-2 pneumonia

Abstract: The acquired hemophilia A (AHA) is a life-threatening condition. The incidence of AHA is extremely low, which requires a multidisciplinary approach to diagnosis and treatment. This is case report of 73-year-old man who presented with AHA secondary to severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2) pneumonia. The patient had extensive skin bleeding and hematomas. In the coagulation screening tests activated partial thromboplastin time (APTT) was prolonged with normal prothrombin time (PT), which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…After selection by title and abstract, 18 records were eligible for inclusion, of which, 3 were review articles [ 7 , 8 , 9 ] and another 3 reported about AHA relapse during or after SARS-CoV-2 infection [ 10 , 11 , 12 ]. Finally, 12 studies (11 full-text articles and 1 conference abstract) were included in the systematic review ( Table 1 ) [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After selection by title and abstract, 18 records were eligible for inclusion, of which, 3 were review articles [ 7 , 8 , 9 ] and another 3 reported about AHA relapse during or after SARS-CoV-2 infection [ 10 , 11 , 12 ]. Finally, 12 studies (11 full-text articles and 1 conference abstract) were included in the systematic review ( Table 1 ) [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…After selection by title and abstract, 18 records were eligible for inclusion, of which, 3 were review articles [7][8][9] and another 3 reported about AHA relapse during or after SARS-CoV-2 infection [10][11][12]. Finally, 12 studies (11 full-text articles and 1 conference abstract) were included in the systematic review (Table 1) [13][14][15][16][17][18][19][20][21][22][23][24]. At the current emergency room (ER) presentation, the patient already had a negative test for SARS-CoV-2 virus infection.…”
Section: Search and Selectionmentioning
confidence: 99%
“…In the last few years, cases of AHA in COVID patients have been described, both after infection and vaccination [15][16][17][18][19][20][21][22][23][24][25]. A few cases of AHA following the viral infection have been reported in literature [15,[26][27][28][29][30]. Our first hypothesis is that SARS-CoV-2 infection acted as the immunological trigger for the development of autoantibodies.…”
Section: Discussionmentioning
confidence: 99%